2015
DOI: 10.17507/tpls.0505.24
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Consciousness-raising vs. Structure-based Production Tasks on Reading Comprehension of Iranian Mid-intermediate EFL

Abstract: Abstract-Task-based instruction is crucial in SLA research, teaching and learning language skills particularly reading comprehension. This study investigated the effect of two kinds of focused tasks on reading comprehension and on the attitudes of Iranians mid-intermediate EFL learners. At first, a pilot study was conducted to see the feasibility of the treatments as well as reliability and validity of the instruments of the study. In the main study, a language proficiency test was used to homogenize the 70 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Slightly different from previous studies, Erfani et al [2015] studied the effects of Consciousness Raising tasks [CR tasks] and SBPTs on reading comprehension. Seventy midintermediate EFL students were offered to participate in.…”
Section: Studies On the Relationship Between Focused Tasks And Studenmentioning
confidence: 98%
See 1 more Smart Citation
“…Slightly different from previous studies, Erfani et al [2015] studied the effects of Consciousness Raising tasks [CR tasks] and SBPTs on reading comprehension. Seventy midintermediate EFL students were offered to participate in.…”
Section: Studies On the Relationship Between Focused Tasks And Studenmentioning
confidence: 98%
“…Briefly, those mentioned studies have demonstrated students' attitudes towards focused tasks and Task-based approach. The majority of them express interests in the new method as it creates more opportunities to engage in communication [Rashtchi, 2012;Erfani et al, 2015]. Nevertheless, some students are hesitant about the new method as they commonly follow the traditional method.…”
Section: Studies On the Relationship Between Focused Tasks And Studenmentioning
confidence: 99%